Integrated microfabricated biodevices advanced technology for genomics, drug discovery, bioanalysis, and clinical diagnostics - Heller, Michael J.; Guttman, Andras (Marcel Dekker, 2002)
Discusses integrated micro fabricated devices such as DNA chips, lab-on-a-chip, micro capillary electrophoresis systems, biosensors, and micro analytical systems. This book reveals how to reach predetermined locations with proteins and orient molecules while preserving their bioactivity.